Genomics of Urea Transport and Catabolism in Cyanobacteria: Biotechnological Implications - Veaudor, Théo; Cassier-Chauvat, Corinne; Chauvat, Franck (Frontiers in Microbiology, 2019)
Cyanobacteria are widely-diverse prokaryotes that colonize our planet. They use solar energy to assimilates huge amounts of atmospheric CO2 and produce a large part of the biomass and oxygen that sustain most life forms. Hence cyanobacteria are increasingly studied for basic research objective, as well as for the photosynthetic production of chemicals of industrial interests. One potential approach to reduce the cost of the future bioproduction processes will be to couple them with the treatment of wastewaters that are often polluted with urea, which in any case is cheaper than nitrate. As yet, however, research has mostly focused on a very small number of model cyanobacteria growing on nitrate. Thus, the genetic inventory of the cyanobacterial phylum is still insufficiently employed to meaningfully select the right host for the right purpose. This review reports what is known about urea transport and catabolism in cyanobacteria, and what can be inferred from the comparative analysis of the publicly available genome sequence of 308 cyanobacteria. We found that most cyanobacteria harbor the genes encoding the urea catabolytic enzymes urease (ureABCDEFG) mostly, but not systematically, together with the urea transport (urtABCDE). These findings are consistent with the capacity of the few tested cyanobacteria to grow on urea as the sole nitrogen source. They also indicate that urease is important for the detoxification of internally generated urea (re-cycling its carbon and nitrogen). In contrast, several cyanobacteria have urtABCDE but not ureABCDEFG, suggesting that urtABCDE could operate in the transport of not only urea but also of other nutrients. Only four cyanobacteria appeared to have the genes encoding the urea carboxylase (uc) and allophanate hydrolase (ah) enzymes that sequentially catabolize urea. Three of these cyanobacteria belongs to the genera Gloeobacter and Gloeomargarita that have likely diverged early from other cyanobacteria, suggesting that the urea carboxylase and allophanate hydrolase enzymes appeared in cyanobacteria before urease.